2013
DOI: 10.2147/ccid.s44865
|View full text |Cite
|
Sign up to set email alerts
|

Skin-protective effects of a zinc oxide-functionalized textile and its relevance for atopic dermatitis

Abstract: Atopic dermatitis (AD) is a chronic inflammatory disease characterized by the impairment of the skin-barrier function, increased oxidative cellular stress, and bacterial colonization. Hence, medical therapies of AD aim to control infection, reduce inflammation, and restore skin-barrier function by use of topical and systemic antibacterial drugs, topical corticosteroids, topical calcineurin inhibitors, and moisturizers. Textiles have the longest and most intense contact with the human skin, and functional texti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(37 citation statements)
references
References 37 publications
1
36
0
Order By: Relevance
“…In recent years, it has been considered that zinc deficiency contributes to various skin conditions such as xerosis and acrodermatitis enteropathica [16, 17]. There is a report that zinc deficiency affects the skin barrier and the immune system and is considered a factor that exacerbates atopic dermatitis [18]. In addition, decrease in serum zinc and increase in histamine levels were observed in dialysis patients experiencing itching, indicating a negative correlation between zinc and histamine levels in these patients [12].…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, it has been considered that zinc deficiency contributes to various skin conditions such as xerosis and acrodermatitis enteropathica [16, 17]. There is a report that zinc deficiency affects the skin barrier and the immune system and is considered a factor that exacerbates atopic dermatitis [18]. In addition, decrease in serum zinc and increase in histamine levels were observed in dialysis patients experiencing itching, indicating a negative correlation between zinc and histamine levels in these patients [12].…”
Section: Discussionmentioning
confidence: 99%
“…To objectively measure the potential antibacterial efficacy of antibacterial fabrics against a S. aureus strain, 5 commercial clothes were enrolled that have documented clinical benefits in treating atopic dermatitis in published reports: Sample #1 (Lyo-Zinc): Benevit Zinc+ (Benevit Van Clewe, Dingden, Germany) which consists of 74% lyocell, 19% SmartCell sensitive fibre, and 7% spandex [16]. Sample #2 (Silk-Aegis): Microair Dermasilk, a pure form of silk consisting exclusively of fibroin and containing a finish of AEGIS AEM 5772/5, an insoluble colorless, odorless ammonium as antibacterial agent [5, 13].…”
Section: Methodsmentioning
confidence: 99%
“…However, whereas some fabrics such as cotton and silk garments tend to reduce scratching by smooth fibre types, a subset of garments have been specifically designed, claiming to reduce the intensity of the eczemas by modulating the skin staphylococcal profile via an antibacterial activity [12, 13]. Some antibacterial clothes therefore use the deposition or incorporation of metallic silver or silver compounds in or onto synthetic fibres [14], whereas others use zinc or quaternary ammonium as antibacterial agents [15, 16]. Subsequently, a number of clinical trials (randomized controlled or observational) were conducted using antibacterial clothes for AD treatment, most of which claimed skin improvements in SCORAD, fewer symptoms, or reduced itching.…”
Section: Introductionmentioning
confidence: 99%
“…They may also offer a plausible solution for cancer and various types of inflammation treatment using, for instance, UV rays with minimal side-effects [39,[48][49][50]. Interesting studies regarding atopic dermatitis revealed that ZnO NPs treatment decreases local skin inflammation on a mouse model with atopic dermatitis [51] and patients with atopic dermatitis [52], as a result of the anti-inflammatory properties of ZnO NPs [51,52], as well as high antioxidative and anti-bacterial capacities [52].…”
Section: Zno Nanoparticles a Variety Of Biomedical Applicationsmentioning
confidence: 99%